Identification of critical intensity from a single lactate measure during a 3-min, submaximal cycle-ergometer test. Issue 22 (17th November 2017) - Fontana, Federico Y.; Colosio, Alessandro L.; Keir, Daniel A.; Murias, Juan M.; Pogliaghi, Silvia
ABSTRACT: We tested the hypothesis that critical intensity in cycling can be determined from a single delta blood lactate in the third minute of a submaximal cycle ergometer trial. Fourteen healthy young men performed four to six constant-power-output trials on a cycle ergometer to the limit of tolerance. Critical intensity was calculated via a linear model and subsequently validated. Lactate was measured at baseline and at 3 min from exercise onset. Delta lactate was the difference between these measures. Based on individual trials, we obtained the delta lactate–% validated critical intensity relationship and thereafter an estimate of critical intensity was computed. Validated and estimated critical intensity were compared by effects sizes, paired-sample t -test and Bland–Altman analysis. Delta lactate was a linear function of the intensity of exercise, expressed as % validated critical intensity ( R 2 = 0.89). Estimated critical intensity was not different from ( d = 0.03, P = 0.98) and highly correlated with ( R 2 = 0.88) validated critical intensity. The bias between measures was 0.03 W (≠0) with a precision of 7 W. The results suggest that critical intensity in cycling can be accurately and precisely determined from delta lactate during a sub-maximal trial and so provides a practical and valid alternative to direct determination.